The 3D GIS software development : global efforts from researchers and vendors - Abdul Rahman, Alias; Zlatanova, Sisi; Pilouk, Morakot (2001)
This paper describes the 3D GIS research efforts done by the GIS research groups as well as by major GIS software vendors world wide, namely Environmental System Research Institute (ESRI) Inc., ERDAS Inc., Integraph Inc., and PCI Geomatics Inc. Research works done by the authors of this paper formed major discussion of this paper including a discussion on why the 3D GIS software is difficult to be realised. At the moment there is no real 3D GIS software available in the GIS market. Hopefully, continuos efforts by researchers in academia and commercial sectors would entailed the most sought 3D GIS software in very near future so that our understanding on real world 3D objects could be improved.